RISK OF HBV REACTIVATION DURING THERAPIES FOR HCC: A SYSTEMATIC REVIEW - Ashari sukahar, Aquarina (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Background: Hepatitis B virus (HBV) reactivation in the setting of immunosuppressive therapy, and in particular chemotherapy, has garnered increasing attention because reactivation can lead to hepatitis, liver failure, and death and also interrupt or delay treatment. The risk of reactivation depends on HBV serological status and the intensity of chemotherapy regimens. HBV reactivation can occur in hepatocellular carcinoma(HCC) treatment such as transarterial chemoemblization (TACE), resection, and radiofrequency ablation (RFA). The aim: This study aims to explain the risk of HBV reactivation during therapies for HCC Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study can show that it meets all requirements. So, experts can ensure that the research is up to date. For this search approach, publications that came out between 2013 and 2023 are taken into account. Several different online reference sources were used to conduct this study. It was decided not to take into account cut reviews, works that have already been published, or works that are only half finished. Result: On the PubMed database, our search results returned 49 articles, while our search results on Sage journal returned 105 articles. Search results conducted since 2013 yielded a total of 34 articles for PubMed and 80 articles for Sage journal. In the end, we compiled a total of 7 articles. We list five eligible studies. Conclusion: HBV reactivation occurs after the curative resection of HBV-related HCC in patients with low hepatitis B viral loads. Postoperative HBV reactivation was related to the recurrence of HBV-related HCC. Use of antiviral therapy and close monitoring of viral loads may be helpful to reduce the recurrence of HBV-related HCC after resection.